Statewide Evaluation of SARS-CoV-2 Diagnoses and Sexual Orientation and Gender Identity. (May 2022) - Jackson, Tracy L.; Chan, Philip A.; Scout, NFN; Nocera, Lauren S.; Crooks, Denise; McCormick, Winston; Bowman, Sarah; Lasher, Leanne; Sarvestani, Amir Sabet; Chambers, Laura C.
Objective: Understanding and identifying disparities in COVID-19 testing outcomes can help allocate resources to where they are most needed. The objective of this study was to estimate the association between lesbian, gay, bisexual, transgender, and queer (LGBTQ+) identity and SARS-CoV-2 test positivity. Methods: Data were from the Rhode Island SARS-CoV-2 surveillance database and included tests scheduled from June 8, 2020, through January 15, 2021. We used multivariable generalized estimating equations accounting for repeat testing to estimate the odds of receiving a positive test result for SARS-CoV-2 by LGBTQ+ identity and race/ethnicity, adjusting for sociodemographic and temporal confounders. Results: In multivariable analysis of 232 025 tests, LGBTQ+ people had lower odds of receiving a positive test result than cisgender heterosexual people (5.4% vs 8.7%; adjusted odds ratio [aOR] = 0.63; 95% CI, 0.59-0.68). Compared with cisgender heterosexual White people, LGBTQ+ White people were significantly less likely (aOR = 0.67; 95% CI, 0.61-0.73) and cisgender heterosexual people of color were significantly more likely (aOR = 1.71; 95% CI, 1.64-1.78) to receive a positive test result. LGBTQ+ people of color had similar test positivity (aOR = 0.90; 95% CI, 0.79-1.02) as cisgender heterosexual White people. People in sexual minority groups were significantly less likely than heterosexual people to receive a positive test result, but we found no significant differences in test results among cisgender, transgender, and gender nonconforming people. Conclusions: LGBTQ+ people may be less likely than heterosexual people to receive a positive test result for SARS-CoV-2, potentially related to protective health practices and greater social isolation. Addressing racial and ethnic disparities among both LGBTQ+ people and cisgender heterosexual people should be a priority of the public health workforce.